Impactos do cuidado na saúde mental de mães de filhos com Transtorno do Espectro Autista e a pandemia do covid-19 - Said, Érika Castelo Branco (My University, 2023)
Autism Spectrum Disorder affects neurodevelopment, causing various impairments in the sphere of social skills, communication difficulties, as well as restricted and stereotyped behavioral patterns, which profoundly affect family dynamics, including care for a child with ASD. Objective: The present study aimed to understand and analyze the impacts of care on the mental health of mothers with children with autism spectrum disorder in the face of the covid-19 pandemic, considering that, the understanding of the disorder, the change in expectations regarding the child, the modification of roles and family routine in the face of the pandemic, can cause illness or promote health, even depending on family coping strategies and the support network. Method: The study was carried out through a qualitative and exploratory research. The study was carried out with 10 mothers of people with ASD in a non-profit institution, specialized in caring for people with autism, in the city of Teresina, state of Piauí. As a reference for analysis, the content analysis of Laville and Dionne was used, whose steps correspond to: 1) Content clipping; 2) Definition of Analytical Categories; 3) Final categorization of the units of analysis. Results and Discussion: It was noticed that most of the interviewed mothers mentioned the absence or little support network to collaborate in the care of the child with ASD, with reports of difficulty in managing time for self-care, with mentions of overload. Most mothers, with regard to the perception of mental health, reported emotional distress, with feelings of hopelessness about the future and nullity. Regarding the impact generated by the pandemic, five of the mothers interviewed stated that their children "enjoyed" the pandemic, and what was worse for them was the return to activities outside the home. For four of the mothers, the common report among them was that during the pandemic it was difficult to deal with the new reality and the complete change in routine. In addition, six of the ten mothers mentioned that they would like more time to do something for themselves, such as going to the gym, studying, working or traveling. Faced with the anxieties that such mothers have, apparently there is also a feeling of loss of self, loss of the right to take care of themselves, or the absence of the possibility of allowing themselves to put their own goals into practice. Final Considerations: The impact on maternal mental health is an event that affects not only the mother, but the entire care and teaching-learning dynamics for the generalization of skills learned in a clinical and educational context. Looking and caring, therefore, for these mothers, is an essential part of intervention therapy in ASD, leading to more effective and more likely to be successful results. [resumo fornecido pelo autor]
O Transtorno do Espectro do Autismo afeta o neurodesenvolvimento ocasionando diversos comprometimentos na esfera das habilidades sociais, dificuldades na comunicação, assim como padrões comportamentais restritos e estereotipados, os quais afetam profundamente a dinâmica familiar, incluindo os cuidados para com um filho com TEA. Objetivo: O presente estudo visou analisar os impactos do cuidado na saúde mental de mães com filhos com transtorno do espectro autista diante da pandemia do covid-19, tendo em vista que, a compreensão do transtorno, a mudança de expectativa quanto ao filho, a modificação de papéis e de rotina familiar diante da pandemia, podem gerar adoecimento ou promover saúde, a depender, inclusive, das estratégias de enfrentamento familiar e da rede de apoio. Método: O estudo foi executado através de uma pesquisa qualitativa e exploratória. O estudo foi realizado com 10 mães de pessoas com TEA em uma instituição sem fins lucrativos, especializada em atendimento a pessoas com autismo, na cidade de Teresina, estado do Piauí. Como referencial de análise, foi utilizada a análise de conteúdo de Laville e Dionne cujas etapas correspondem a: 1) Recorte de conteúdos; 2) Definição de Categorias Analíticas; 3) Categorização final das unidades de análise. Resultados e Discussão: Percebeu-se que a maioria das mães entrevistadas referiu ausência ou pouca rede de apoio para colaborar nos cuidados com o filho com TEA, havendo relatos de dificuldade de gerenciamento do tempo para o cuidado de si, com menções de sobrecarga. A maioria das mães, no que diz respeito à percepção da saúde mental, referiu sofrimento emocional, com sentimentos de desesperança quanto ao futuro e nulidade. Com relação ao impacto gerado pela pandemia, cinco das mães entrevistadas afirmaram que seus filhos "gostaram" da pandemia, e o que foi pior para elas foi a volta das atividades fora de casa. Para quatro das mães o relato comum entre elas foi de que durante a pandemia foi difícil lidar com a nova realidade e a mudança completa da rotina. Além disso, seis das dez mães referiram que gostariam de mais tempo para fazerem algo para si, como ir à academia, estudar, trabalhar ou viajar. Diante dos anseios que tais mães possuem, aparentemente também existe o sentimento de perda de si, perda do direito de cuidado de si mesmas, ou ausência da possibilidade de se permitirem colocar em prática seus objetivos próprios. Considerações Finais: O impacto na saúde mental materna é um evento que afeta não apenas a mãe, mas toda a dinâmica de cuidado e de ensino-aprendizagem para generalização de habilidades aprendidas em contexto clínico e educacional. Olhar e cuidar, portanto, essas mães, é uma parte essencial da terapêutica de intervenção no TEA, conduzindo a resultados desejados para o desenvolvimento global da criança com TEA. [resumo fornecido pelo autor]
Keywords: Transtornos do espectro autista; Maternidade; Saúde mental; Pandemias; COVID-19; Autism spectrum disorders; Motherhood; Mental health; Pandemics